MyomiRs as Markers of Insulin Resistance and Decreased Myogenesis in Skeletal Muscle of Diet-Induced Obese Mice - Frias, Flávia de Toledo; de Mendonça, Mariana; Martins, Amanda Roque; Gindro, Ana Flávia; Cogliati, Bruno; Curi, Rui; Rodrigues, Alice Cristina (Frontiers in Endocrinology, 2016)
High-fat diet (HFD) feeding causes insulin resistance in skeletal muscle of mice, which affects skeletal muscle metabolism and function. The involvement of muscle-specific microRNAs in the evolution of skeletal muscle insulin resistance during 4, 8, and 12 weeks in HFD-induced obese mice was investigated. After 4 weeks in HFD, mice were obese, hyperglycemic and hyperinsulinemic, however, their muscles were responsive to insulin stimuli. Expressions of MyomiRs (miR-1, miR-133a, and miR-206) measured in soleus muscles were not different from those found in control mice. After 8 weeks of HFD feeding, glucose uptake was lower in skeletal muscle from obese mice compared to control mice and we observed a significant decrease in miR-1a in soleus muscle when compared to the 4 weeks group. miR-1a expression continued to decay within time. After 12 weeks of HFD, miR-133a expression was up regulated when compared to the control group. Expression of miR-1a was negatively correlated with glycemia and positively correlated with the constant rate of plasma glucose disappearance. Pioglitazone treatment could not reverse decreases of miR-1a levels induced by HFD. Targets of myomiRs involved in IGF1 pathway such as Igf1, Irs-1, Rheb, and follistatin were reduced after 12 weeks in HFD and Mtor increased, when compared to the control or HFD for four or eight weeks. These findings suggest for the first time that miR-1 may be a marker of the development of insulin resistance in skeletal muscle. Evidence was also presented that impairment in myomiRs expression contributes to decreased myogenesis and skeletal muscle growth reported in diabetes.